Perspektif Teori Belajar Kognitif pada Penerapan Pembelajaran Berbasis Masalah Bagi Siswa Kelas 4 SD Negeri 2 Banyuning - Maharani, Ida Ayu Gde Sutha; Suarni, Ni Ketut; Margunayasa, I Gede (Universitas Batanghari Jambi, 2025)
This research aims to investigate the impact of implementing Problem Based Learning (PBM) with a Cognitive Learning Theory perspective on the learning understanding of grade 4 students at SD Negeri 2 Banyuning. Using a qualitative approach, exploring student involvement in the learning process, effectiveness of PBM, and comparison of results with a control group that did not implement PBM. The results showed significant differences between the experimental and control groups, with the experimental group showing a better increase in learning understanding. This research contributes to a practical understanding of the effectiveness of PBM with a cognitive approach in improving grade 4 students' overall understanding of learning.